A STUDY ON STRESS MANAGEMENT AMONG SELF FINANCING COLLEGE FACULTIES OF CALICUT DISTRICT - Swathikishore; Baby (International Journal of Research -GRANTHAALAYAH, 2017)
Stress is a term generally used to define state of mind of tensions or tiredness usually associated with work overload or overly demanding work. Stress is ordinary phenomenon in an individual’s daily life.Stress refers to the anxiety from the conflict between our external environment and us, leading to emotional and physical pressure. The main aim of the study is to identify the stress level of faculty members working in self-financing colleges situated in Calicut District. The study is conducted on Faculties of Self finance colleges. Faculties from many self-financing colleges are taken consideration and the sample size is 200. Simple random sampling was adopted for this study. The findings stated that majority 55.5% of faculties having stress related symptoms and 21.5% of faculties doing Meditation and Exercise to reduce stress. The study concluded that the most important causes for stress among faculties are overloaded working hours, role in the performance of job, student discipline, innovations in the higher education field, career development, funding policies, problems arise from administration side, feeling of angry, whipping by finished tiredness and unfit to move in work are considered as the essential results of stress among the Arts and Science school instructors.